ANALISIS PROBLEMATIKAN PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Siti Yuliana Hasibuan; Aliya Nur Hasybi; Ary Yantyi Siregar; Khotna Sofiyah (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to identify and analyze the mathematical problems faced by students in elementary schools. The main focus of this study is to understand the obstacles that arise in learning mathematics and the factors that influence them. The methodology used in this study is a qualitative approach with in-depth interview techniques with teachers and classroom observations in several elementary schools in urban and rural areas. The results of the study indicate that the main problems faced by students in learning mathematics are the lack of understanding of basic concepts, limited time allocated for mathematics subjects, and the lack of interesting learning resources and media. In addition, student motivation factors and parental support also play an important role in the success of mathematics learning in elementary schools. This study provides recommendations for improvements in teaching methods and improvements in supporting facilities for mathematics learning in elementary schools.